Computational Study of D-glucose and its Differential Cognitive Effects on Well-being and Quality of Life - Nadeem, Sohail; Mohyuddin, Ayesha; Javed, Mohsin; Hafeez, Abdul; Jamil, Tayyaba; Tahir, Fatima; Raza, Hamid; Haroon, Shah Muhammad; Umer Aslam, Hafiz Muhammad; Arif, Muhammad (Scientific Inquiry and Review, 2020)
GAMESS computational chemistry package is a freeware available on the web. It has been successfully applied for the structure elucidation of the commonly available D-glucose. In the current research, IR and Raman spectra of D-glucose were theoretically calculated by utilizing the density functional theory (DFT), combined with B3LYP/3-21G basic set. IR and Raman activities were estimated through the GAMESS computational package. Moreover, the NMR spectrum was also obtained through the Gaussian 09 package. Theoretically calculated and experimentally calculated results were compared using the B3LYP/3-21G level of theory. The results of both calculations were nearly the same. The optimization of structure with the various levels of theory and Basis sets was studied and the best results were obtained using B3LYP/3-21G, and these results agreed considerably with the experimental results. The current computational analysis may be useful to predict complex carbohydrate precursors and other carbohydrate molecules. Copyright(c) The Authors